POPLINK - Demographic database, Umeå university (Umeå University, 2014)
The database POPLINK is a longitudinal population database under construction with the support of Riksbankens Jubileumsfond and Umeå University. The database contains personal data of the regions Umeå and Skellefteå during the period 1700-1950. In the beginning of 2014, there was information on approximately 600 000 individuals, 3,3 millions entries and up to 15 generations. This makes POPLINK to one of the world’s largest and most detailed population databases.

The database is a resource in many areas of research. Not least because of the possibility to link together POPLINK with other modern registers. This means, among other things, that the life sciences can investigate how nature and nurture influence the development of our most common national diseases, such as cardiovascular diseases, cancer, and diabetes. Within the social sciences and the humanities, the increasing access to personal records brings about an opportunity for new perspectives on the rise of the welfare state and the time that shaped the modern Sweden.

POPLINK is a research database, which means that only academic researchers can be given access after approval from the Regional Ethical Review Board.

Purpose:

The Demographic Database (DDB) is a special unit at Umeå University with activities focused on two main areas: data production and research. DDB creates and makes available population databases, mainly based on historical information in parish registers during the 18th, 19th, and 20th centuries.

POPLINK är en ny forskningsinfrastruktur som Demografiska databasen håller på att bygga upp med stöd från Riksbankens Jubileumsfond och Umeå universitet. Databasen innehåller individdata från Umeå- och Skellefteåregionen för tiden 1700 till 1950. I början av 2014 fanns information om cirka 600 000 individer, 3,3 miljoner poster och uppemot 15 generationer. Detta gör POPLINK till en av världens allra största och mest detaljerade befolkningsdatabaser.

Databasen är en resurs för många vetenskapsområden. Inte minst eftersom det går att koppla ihop POPLINK med moderna register. Det innebär exempelvis att livsvetenskaperna kan studera hur arv och miljö påverkar utvecklingen av våra vanligaste folksjukdomar, som hjärt- och kärlsjukdomar, cancer och diabetes. Inom samhällsvetenskap och humaniora öppnar den ökade tillgången till digitala individdata för nya perspektiv på välfärdsstatens framväxt och den tid som formade det moderna Sverige.

POPLINK är en ren forskningsdatabas. Det innebär att endast akademiska forskare kan få tillgång till den efter godkänd prövning i regional etikprövningsnämnd.

Syfte:

Demografiska databasen (DDB) är en särskild enhet vid Umeå universitet med inriktning på dataproduktion och forskning. DDB skapar och tillgängliggör befolkningsdatabaser, främst baserade på historisk information från kyrkböcker från 1700-, 1800- och 1900-talen.
POPLINK - Demografiska databasen
Keywords: diseases; sjukdomar; inheritance; arv; physical activities; fysisk aktivitet; demography; demografi; demographic statistics; demografisk statistik; development; utveckling; families; familjer; social change; social förändring; Physical Education and Training; Fysisk fostran och träning; SwedPop; SwedPop; Censuses; Folkräkningar; Economic conditions and indicators; Ekonomiska förhållanden och indikatorer; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; General health and well-being; Allmän hälsa och välbefinnande; History; Historia; Diet and nutrition; Kost och näring